A review of solar still performance with reflectors. (February 2017) - Omara, Z.M.; Kabeel, A.E.; Abdullah, A.S.
Abstract: In numerous respects, the solar still is a perfect wellspring of freshwater for both agriculture and drinking in remote areas or islands. There are numerous sorts of solar stills; the least difficult and most demonstrated is the basin solar still (conventional solar still). Investigations demonstrated that the conventional still has constrained productivity. Scientists have taken efforts to make diverse designs of solar stills to improve the productivity and deduced that solar stills integrated with reflectors are one of the most efficient and effective designs. The reflectors, either external or internal, are a good and cheap modification to increase the solar irradiation directed to the basin liner or the water as well as the distillate efficiency of the still. In this paper, a broad survey for diverse solar stills with reflectors has been conducted.